Capitalism, culture, and decline in Britain, 1750-1990 - Rubinstein, W. D. (Routledge, 1993)
This original and controversial contribution to the topical debate on Britain's economic decline presents a critique of the thesis made familiar in recent years by Martin J. Wiener, Anthony Sampson, Correlli Barnett and others.
Keywords: Great Britain -- Economic conditions.; Elite (Social sciences) -- Great Britain -- History.; Great Britain -- Social conditions.; Great Britain -- Politics and government.; Grande-Bretagne -- Conditions économiques.; Élite (Sciences sociales) -- Grande-Bretagne -- Histoire.; Grande-Bretagne -- Conditions sociales.; Grande-Bretagne -- Politique et gouvernement.; POLITICAL SCIENCE -- Economic Conditions.; BUSINESS & ECONOMICS -- Economics -- Comparative.; BUSINESS & ECONOMICS -- Economic Conditions.; BUSINESS & ECONOMICS -- Economic History.; Economic history; Elite (Social sciences); Politics and government; Social conditions; Great Britain; Economic conditions -- Related to -- Sociology; Electronic books.; History